A Study of Long-Run Equilibrium Relationship Between Foreign Direct Investment and Its Key Determinants in Malaysia - Rosli, Mohd Fairuzz; Zaghlol, Dr. Azlul Kalilah; Soo Cheng, Associate Professor Dr. Chuah; Mohd Shakil, Dr. Nurul Syifaa; Goh, Theng-Huey (Information Management and Business Review, 2024)
This study investigates the long-run equilibrium relationship between foreign direct investment (FDI) and its key determinants in Malaysia. Employing the Autoregressive Distributed Lag (ARDL) model on annual data between 1971 and 2021. The key findings confirm a long-run equilibrium relationship between FDI and the selected macroeconomic variables as a group. However, the individual impact of gross domestic product, inflation, exchange rate, and trade openness on FDI is not statistically significant when analyzed separately. Specifically, the long-run results suggest that the determinants do not have significant effects on FDI. Meanwhile, the short-run relationship between FDI and its determinants in Malaysia reveals a complex interplay of factors. Inflation and exchange rates play significant roles, with inflation generally encouraging FDI and exchange rate volatility creating mixed effects. Trade openness on the other hand shows some short-run significance but it is not consistently impactful. The error correction (ECM) model also confirms the existence of a long-run relationship. It highlights that while short-term fluctuations can occur, FDI tends to move towards a long-term equilibrium influenced by a relatively moderate speed of adjustment. The key conclusion implies that FDI is influenced by the combined effect of these variables in the longer term, but the individual contribution of each variable is not strong enough to stand out statistically. This research contributes to the understanding of FDI dynamics in Malaysia by providing insights, thereby informing policymakers and investors about effective strategies to attract and leverage FDI for sustainable development.